Strategi Guru dalam Menerapkan Materi P5 Tema Kearifan Lokal pada Pembelajaran Sosiologi Kelas X SMAN 1 Kalidawir Tulungagung - Bilqis Bilbina; Yudi Krisno Wicaksono (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research was motivated by the importance of implementing the merdeka curriculum, which emphasizes character development through the Pancasila Student Profile Strengthening Project (P5), particularly within the theme of local wisdom. Preliminary findings indicated that prior to the implementation of P5, students had limited understanding of social issues such as bullying, discrimination, and diversity. Therefore, appropriate teaching strategies are required to shape students’ character and enhance their social awareness The research questions addressed in this study are: (1) What strategies do teachers use to implement P5 material with the theme of local wisdom in Sociology learning for Grade X students at SMAN 1 Kalidawir? (2) What are the impacts of the applied strategies on the learning process? (3) What challenges do teachers face in implementing these strategies?. This study employs a qualitative descriptive research design. The aim is to explore the strategies used by teachers, their impacts on students, and the challenges encountered during the implementation of P5 materials. Data were collected through observation, interviews, and documentation. The findings of the study show that: (1) Teachers implemented project-based, collaborative, and contextual learning strategies that involved the local environment as a learning resource. (2) These strategies had a positive impact on students’ understanding of local cultural values and encouraged attitudes of tolerance and social awareness. (3) Challenges faced by teachers included limited time, varying levels of student motivation, and insufficient supporting facilities. Despite these obstacles, teachers strived to overcome them through collaboration, innovative learning approaches, and student-centered methods.